Emerging Technologies and Coral Reef Conservation: Opportunities, Challenges, and Moving Forward - Madin, Elizabeth M. P.; Darling, Emily S.; Hardt, Marah J. (Frontiers in Marine Science, 2019)
Coral reefs worldwide are declining at an accelerating rate due to multiple types of human impacts. Meanwhile, new technologies with applications in reef science and conservation are emerging at an ever-faster rate and are simultaneously becoming cheaper and more accessible. Technology alone cannot save reefs, but it can potentially help scientists and conservation practitioners study, mitigate, and even solve key challenges facing coral reefs. We examine how new and emerging technologies are already being used for coral reef science and conservation. Examples include drones, autonomous underwater vehicles (AUVs), 3D mapping and modelling tools, high-resolution and nano-satellite imagery, and a suite of monitoring and surveillance tools that are revolutionizing enforcement of sustainable reef fisheries. We argue that emerging technologies can play a pivotal role in tackling many of the critical issues facing coral reef conservation science and practice, but maximizing the impact of these technologies requires addressing several significant barriers. These barriers include lack of awareness of technologies and tools, prohibitive cost, lack of transferability across systems and/or scales, lack of technical expertise, and lack of accessibility. We discuss where analogous challenges have been overcome in another system and identify insights that can provide guidance for wise application of emerging technologies to coral reef science and conservation. Thoughtful consideration of, and adaptation to, these challenges will help us best harness the potential of emerging and future technological innovations to help solve the global coral reef crisis.